Yogicchakra symbols: Mirrors of the human mind/heart - Meadow, Mary Jo (Journal of religion and health, 1993)
This paper describes the classical understanding of the system ofchakras, or centers of spiritual energy, in tantric yoga. Eachchakra is presented in terms of its traditional understanding. Each is also discussed in the light of contemporary psychological stage theories of development, showing that thechakras can be seen as a model of spiritual development. The preoccupations, concerns, and attitudes associated with eachchakra are portrayed as a mirror of the human mind/heart when spiritual energy is concentrated at that location.